Alat Pendeteksi Kebakaran Dini Berbasis Internet Of Things (IoT) Menggunakan NodeMCU Dan Telegram - Yonatan Surya Kristama; Indrastanti Ratna Widiasari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
One of the unpredictable disasters is fire. Fires often occur in densely populated areas and are triggered by a variety of factors, for example an electric short circuit. Usually a fire disaster is only realized when the fire has grown and has spread to all places. Based on these problems, a solution is needed to prevent the occurrence of fire disasters, namely by designing an Early Fire Detection Tool Based On Internet of Things (IoT) Using NodeMCU And Telegram. The microcontroller used in this study is NodeMCU which is equipped with WiFi ESP8266. This tool uses two fire sensors, namely the LM393 type fire sensor and the KY-026 type fire sensor, besides that this tool also uses buzzer which is used to provide warnings in the form of sound and Light Emitting Diode which are used as a sign that the microcontroller is connected to Telegram. This study produces a device that can send notifications in the form of messages to the user's telegram if the two fire sensors detect the presence of fire in which the two fire sensors can detect the source of the fire up to a distance of 50 cm. This tool can make it easier for users to monitor the condition of the room in real - time by sending messages through the telegram application and this tool will reply to the message automatically according to the conditions of the two fire sensors.